Transformasi Digital untuk Praktik Berkelanjutan dalam Bidang Digital Finance, Blockchain dan Cryptocurrencies, dan E-Goverment - Kurniawati, Yulia Ery; Halim, Erwin; Mailangkay, Adele BL; Syamsuar, Dedy (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
Digital transformation is developing rapidly and has become a global trend. It encourages sustainable practices in various sectors. These sectors include digital finance, blockchain and cryptocurrency, and e-Government. This Community Service (PkM) is three sessions from the NUNI IT Online Seminar Phase 6 with the topic